Althusser against functionalism. Towards the concept of ‘overinterpellation’ - Pippa, Stefano (Universidad de Costa Rica, 2020)
This article re-reads Althusser’s theory of ideology based on the original manuscript from which the famous 1970 essay on Ideology was culled. It aims to counter the standard critique of functionalism levelled against Althusser, and it does so by arguing that Althusser’s theory of ideology is better grasped through the concept of ‘overinterpellation’.